Echocardiographic characterization and markers of cardiovascular risk in adults with sickle cell disease in a Colombian tertiary referral centre: A cross-sectional study - Martin E. Arrieta-Mendoza; Juan R. Betancourt; Sebastián Ayala-Zapata; Stephany Barbosa-Balaguera; Christian D. Messu-Llanos; Juan P. Rosales-Melo; Darío F. Andrade-Hoyos; Álvaro Herrera-Escandón; Oswaldo E. Aguilar-Molina (PLoS ONE, 2026)
Sickle cell disease (SCD) is associated with substantial cardiovascular morbidity, but echocardiographic data from Latin American populations remain scarce. We aimed to characterise the structural, functional, and haemodynamic echocardiographic profile of adults with SCD attending a tertiary referral centre in Cali, Colombia. We conducted an observational, cross-sectional study based on systematic review of medical records and transthoracic echocardiography reports of consecutive adult patients (≥18 years) with confirmed SCD evaluated between January 2022 and December 2024. Patients with complex congenital heart disease, severe valvular disease of unrelated aetiology, pregnancy, or echocardiograms of insufficient quality were excluded. Of 669 patients screened, 57 met inclusion criteria. Reporting followed STROBE recommendations. The median age was 24 years (interquartile range [IQR] 21–32) and 59.6% were female; the SS genotype was the most frequent (76.4%) and 68.5% were on hydroxyurea. Median haemoglobin was 8.5 g/dL (IQR 7.1–10.0) and median NT-proBNP 491 pg/mL (IQR 98–1290). Most patients had preserved left ventricular dimensions and systolic function (median ejection fraction 63%, IQR 57–66.5; mean global longitudinal strain −18.9% ± 2.9). Right ventricular function was preserved (mean tricuspid annular plane systolic excursion 25.4 ± 4.6 mm). Left ventricular geometry was normal in 42.1%, with concentric remodelling in 10.5%, concentric hypertrophy in 21.1%, and eccentric hypertrophy in 26.3%. Diastolic function was normal in 71.4%. Valvular disease, when present, was predominantly mild. Tricuspid regurgitation velocity exceeded 2.5 m/s in 14 of 36 patients with measurable TRV (38.9%; 24.6% of the whole cohort) and exceeded 3.0 m/s in 6 patients (16.7% of those with measurable TRV), identifying a substantial subgroup at intermediate-to-high probability of pulmonary hypertension. In this Colombian cohort of relatively young adults with SCD, cardiac structure and biventricular function were largely preserved, but nearly one-third of patients had echocardiographic findings suggestive of pulmonary hypertension. These findings support the routine use of transthoracic echocardiography as an accessible tool for early cardiovascular risk stratification in adults with SCD in low- and middle-income settings.